2013
DOI: 10.1007/s10484-013-9222-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Function Associated with Treatment Adherence After a Brief Intervention in Patients with Chronic Pain

Abstract: The goal of this study was to investigate psychophysiological characteristics in chronic pain patients during a pain stressor (cold pressor test) and after a brief diaphragmatic breathing intervention. Laboratory procedures were designed to quantify the effects of diaphragmatic breathing training at six breaths per minute on cardiac autonomic reactivity as indexed by root mean square of successive differences (RMSSD) and sequential baroreflex sensitivity (sBRS). Participants (n = 22) completed an initial labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This might lead to a hypothesis that, for example, a psychophysiological decoupling might exist at baseline and would be unset by TAU, eventually leading to a higher expression of psychophysiological answers. Previous studies on this topic could not be identified but, according to the literature available, a psychophysiological mismatch of patients with somatoform disorders is described in existing evidence (Evans et al, 2013;Pollatos et al, 2011;Rief & Auer, 2001;J. E. Schmidt, Joyner, Carlson, & Hooten, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to a hypothesis that, for example, a psychophysiological decoupling might exist at baseline and would be unset by TAU, eventually leading to a higher expression of psychophysiological answers. Previous studies on this topic could not be identified but, according to the literature available, a psychophysiological mismatch of patients with somatoform disorders is described in existing evidence (Evans et al, 2013;Pollatos et al, 2011;Rief & Auer, 2001;J. E. Schmidt, Joyner, Carlson, & Hooten, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, previous studies have shown that sympathetic nervous system (SNS) activity decreases, as evidenced by changes in HR and blood pressure, while parasympathetic nervous system (PSNS) activity increases, as revealed by changes in HRV indices and sBRS. 24 , 30 , 37 , 40 These physiological changes have been associated with a reduction in symptoms of chronic pain syndromes, including fear, anxiety, and catastrophizing. 18 , 38 , 39 , 49 By understanding the mechanisms behind the therapeutic effects of slow-paced breathing, treatments can be refined and applied to other chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Several recently published studies have demonstrated improvements in pain and other FM-related symptoms in patients after training in a breathing-focused intervention. 18 , 37 , 38 Specifically, heart rate variability (HRV) biofeedback paired with slow-paced breathing has demonstrated efficacy in the improvement of pain severity and functioning in FM. 18 However, the underlying physiological changes associated with the efficacy of these interventions are not well understood.…”
Section: Introductionmentioning
confidence: 99%